Good Governance dalam Pengelolaan Dana Desa di Desa Menjangan Kecamatan Bojong Kabupaten Pekalongan - Savitri, Niken Oktadiana; Setianingsih, Endang Larasati; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2024)
The government provides substantial funds to village governments in an effort to accelerate the process of equitable development in Indonesia. To be able to realize clean government and good governance, there are four main characteristics, namely participation, transparency, rule of law and accountability. Whether or not the government succeeds in striving to realize good governance is determined by how much the principle is implemented. This study aims to analyze the application of good governance principles in the management of village funds and analyze the obstacles faced in applying good governance principles to the management of village funds. This research uses descriptive qualitative methods with data collection through observation, interviews and documentation. The results showed that the management of village funds in Menjangan Village has applied the four principles of good governance, namely transparency, participation, rule of law and accountability. This is evidenced by the Menjangan Village Government's efforts in managing village funds, namely the implementation of hamlet deliberations, musrenbangdes, installation of infographics, installation of activity boards, supervision from the community to the Inspectorate and the creation of a suggestion box. However, in its implementation, there are obstacles, namely transparency in the management of village funds that have not been optimized due to limited village government resources in the field of information technology, limited sources of village information media, and installation of infographics only at the Village Hall. Another obstacle faced in the management of village funds is the lack of optimal community participation, especially during village meetings.